Phytochemical Constituent, Antibacterial and Antioxidant Leaves of Dracaena trifasciata (Prain) Mabb. - Whika Febria Dewatisari; Nelsiani To'bungan (UIN Sunan Gunung Djati Bandung, 2024)
Sansevieria, commonly known as Dracaena trifasciata. Apart from serving as an ornamental and air-purifying plant, it also exhibits medicinal properties, making it a potential candidate for the development of novel natural drugs. The demand for natural antibacterial agents has significantly increased due to the rising incidence of resistance among pathogenic bacteria, such as Staphylococcus aureus. This research conducted to determine the antibacterial and antioxidant activities of D. trifasciata leaf extracts. The D. trifasciata leaf material was sequentially extracted using sonication, beginning with chloroform and then followed by ethanol. The Kirby-Bauer method was employed to conduct the antibacterial test, wherein the inhibition zones generated by the chloroform and ethanolic extracts were measured. The test bacteria used in this study was Staphylococcus aureus. The assessment of the antioxidant activity was conducted using the DPPH (2,2-diphenyl-1-picrylhydrazyl) method. Phytochemical compound identification in the extracts was conducted using GC-MS analysis. The ethanolic extract showed a higher yield percentage compared to the chloroform extract. Both extracts exhibited moderate antibacterial activity. The chloroform extract exhibited an inhibition zone of 73.33 mm2, while the ethanolic extract showed an inhibition zone of 110 mm2. The chloroform extract had a minimum inhibitory concentration (MIC) of 500 mg/mL and a minimum bactericidal concentration (MBC) of 1000 mg/mL. The ethanolic extract had an MIC of 31.25 mg/mL and an MBC of 62.50 mg/mL. In terms of antioxidant activity, the chloroform extract had an IC50 of 370.8±0.07 µg/mL, while the ethanolic extract had an IC50 of 647.4±0.12 µg/mL. GC-MS analysis revealed 47 compounds in the chloroform extract and 49 compounds in the ethanolic extract. Based on the results of yield, antibacterial and compound identification, the ethanolic extract of D. trifasciata leaves exhibited greater potential compared to the chloroform extract. Its antibacterial activity showed more promise than its antioxidant activity